The Social Conditions in the Ma’an District, Jordan in 1962 AD Regarding Two Reports of the Steering Committee for the Relief and Improvement of Services in the Southern District - ALQudah, Ahmad Hamed Ibraheem (Jordan Journal for History and Archaeology, 2024)
The Steering Committee for the Relief and Improvement of Services in the Southern District (of Jordan) was formed by Wasfi al-Tal’s government on March 17, 1962 and included the undersecretaries of the Ministries of Interior, Health, Agriculture, and Social Affairs, in addition to the commander of the Military Brigade in Ma‘an. In order to become familiar with the problems that the residents of this district suffered from and the aid and projects that they needed, the committee members visited the Ma‘an District on 19/3/1962 AD, and submitted two reports to the Prime Minister Wasfi Al-Tal: the first on 24/3/1962 AD, and the second on 3/27/1962 AD. These two reports included information on the social conditions in the Ma‘an District. One of the reasons for the instability of most of the residents of the Ma‘an District was their lack of ownership of agricultural lands and the lack of operational projects that encouraged them to settle. This research highlights that information, especially with regard to the tribes inhabiting the Ma‘an District, their sources of income and material conditions, the suggestions put forward by the Steering Committee to improve them, and the assistance provided by the government as southern aid, and by American charities, and the Steering Committee’s opinion about them. It also discussed a housing units project, the opinion of the Steering Committee, and the government’s position on the committee’s reports on the project, and a statement of the most prominent demands of the residents of Ma‘an District about education. The formation of the Steering Committee for Relief and Improvement of Services in the Southern District revealed the keenness of Wasfi al-Tal’s government to study the problems on the ground and to develop appropriate solutions for them in the interest and benefit of the citizens.